Ratiometric glyco-probe for transient determination of thiophenol in full aqueous solution and river water. (May 2015) - Li, Kai-Bin; Zhou, Dan; He, Xiao-Peng; Chen, Guo-Rong
Abstract: Although being widely used in organic synthesis, thiophenol (Tp) is toxic to the human body. We report here the preparation of a ratiometric fluorescence probe for the selective, transient determination of Tp in full aqueous solution. The probe was synthesized by a click reaction coupling between an alkynyl naphthalimide-dansyl dyad and an azido galactoside which increases the water solubility. Fluorescence spectroscopic analyses showed that the probe had a specific ratiometric response to Tp transiently in a full aqueous solution, over a range of other species. The probe has also proven suitable for the quantification of Tp in environmental water samples, and possesses superior properties to previous Tp fluorescence probes in terms of water solubility and sensitivity. Graphical abstract: Highlights: Glyco-naphthalimide probe is developed for thiolphenol (Tp). The probe shows ratiometric response to Tp. The detection is transient in full aqueous solution. Tp in real river water samples can be accurately quantified.